Uso de e-mental health para el seguimiento posterapia de pacientes con depresión en Colombia (2017)
ABSTARCT: Use of E-Mental Health for monitoring depressive patients in Colombia Depressive disorders affect people of all ages, they reduce the quality of life and are recurrent. The most recent reports of the Ministry of Health and Social Protection establish between 12,1 and 13,1 % the prevalence of depression in the Colombian population. In recent years, the field of e-mental health has expanded rapidly and interventions based on communication and information technologies are being suggested as means to complement conventional mental health services. In this context, the research had as purpose to evaluate in Colombia the feasibility and acceptability of the technological intervention called “Apoyo, Seguimiento y Control de Enfermedades a partir de Sistemas Operativos –ASCENSO”. A purposive sample of patients discharged from psychotherapeutic treatments was selected. The HPQ-9 was applied, the ASCENSO platform was implemented, and finally, semi-structured interviews were conducted with study participants. The results show a favorable opinion of the patients that participated, the difficulties of the mental health institutions to join a project like this and a sensible lack of e-mental health programs in Colombia.